The scientific worldview and rejection of soul : a critical analysis - Hasan, Md Maruf (Abu Hamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences,International Islamic University Malaysia, 2022)
The academic and popular debates on science and religion have reached an impasse. Both sides seem to provide mutually exclusive claims. This research attempts to pave an alternative route in this debate. This research takes the field of Islamic spirituality—known as Tazkiyat Al-Nafs—and puts it in conversation with the scientific worldview. The conversation will highlight an original approach in which Islam can critically engage with the latest scientific-based ideologies. This study aims at investigating whether Tazkiyat Al-Nafs or the scientific worldview is better at providing practical solutions to practical life that is of concern to every individual. The study explores the origins, history, and current formulation to the scientific worldview. It also explores the unique features and characteristics of Islamic spirituality. Finally, it contrasts both the scientific worldview and Tazkīyat Al-Nafs and concludes that, at least in relation to practical living, Tazkīyat Al-Nafs is more useful than the scientific worldview. This study uses the comparative approach to studying different worldviews; it also uses critical reading of textual sources, alongside situating fresh interpretations of classical themes via the use of postmodern theology. The study’s primary conclusion is that both atheists and theists, non-Muslims and Muslims can benefit from the practical wisdom found in Tazkiyat Al-Nafs. A secondary conclusion is that there is no contradiction between Islam and science; rather, the contradiction only occurs between Islam and the scientific worldview. Science is not equal to the scientific worldview. The research hopes to have laid the theoretical foundation for further exploration of Islamic spirituality and its engagement with the modern world and postmodern concerns